2011
DOI: 10.1097/med.0b013e3283446ed2
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes in pregnancy: glycemia control guidelines and rationale

Abstract: Purpose of review Little consensus exists on the definition of gestational diabetes (GDM), how the condition should diagnosed, and if interventions for mild maternal hyperglycemia are of any benefit to the mother or fetus. Today, after several large multi-center clinical trials, we are closer than ever to a national and international consensus. Recent findings Glucose tolerance in pregnancy is a continuum, which has a fundamental link to fetal growth. The relationship between maternal glycemia and adverse ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
11
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 16 publications
1
11
0
Order By: Relevance
“…In our study, the differences among the groups were not statistically significant, similar to previously published data demonstrating that the high glucose levels in the maternal circulation are associated with increased birth weight (25,26). The absence of significant differences in the incidence of adverse obstetric outcomes among the groups may be partly attributed to intervention for GDM, as the results of a previous study which demonstrated that timely intervention for GDM significantly reduced the rate of certain adverse obstetrical outcomes (27).…”
Section: B a B Asupporting
confidence: 89%
“…In our study, the differences among the groups were not statistically significant, similar to previously published data demonstrating that the high glucose levels in the maternal circulation are associated with increased birth weight (25,26). The absence of significant differences in the incidence of adverse obstetric outcomes among the groups may be partly attributed to intervention for GDM, as the results of a previous study which demonstrated that timely intervention for GDM significantly reduced the rate of certain adverse obstetrical outcomes (27).…”
Section: B a B Asupporting
confidence: 89%
“…A key point of debate during this revision process has been whether early pregnancy screening for GDM should be offered universally for all women or selectively to sub‐populations at higher risk of T2DM . Furthermore, the type of tests (particularly in early pregnancy) , the timing of tests, what thresholds should be used , as well as the most effective preventive, treatment and follow‐up strategies continue to be discussed . However, one area of apparent consensus is that women in sub‐populations at high risk of T2DM should be offered screening in early pregnancy at 6–12 weeks of gestation , in addition to screening at 24–28 weeks of gestation as is currently recommended.…”
Section: Introductionmentioning
confidence: 99%
“…Although a fraction of these women may have unrecognized pre-gestational diabetes, most of them have GDM or pregnancy-related glucose intolerance from several epidemiological studies (Coetzee, 2009;Damm, 2009;Ma and Chan, 2009;Seshiah et al, 2009). Hyperglycemia is the essential characteristic in gestational diabetes or in pregnancies of women with pre-existing diabetes (Karakash and Einstein, 2011;Lacroix et al, 2013). Glucose can transport across the placenta, and glucose fluctuation not only affects the metabolic status of pregnant women but also interferes with fetal development (Hay, 2006).…”
mentioning
confidence: 99%